The Role of Large Corporations of Non-Ferrous Metallurgy in Providing Revenues of Regional Budgets Illustrated by Krasnoyarsk Territory (the public company ‘Norilsk Nickel’) and Irkutsk Region (the public company ‘OK RUSAL’) - M. K. Malyshev (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
Invariably high role of large tonnage and low-added-value business in economy of the Russian Federation stipulates topicality of such research. Big business reaching 78-80% of Russian GDP will continue playing the primary role, which will be backed by exchange rate in exporters’ interests and their raw material orientation. Iron and steel industry in Russia by budget, production and export significance yields only to oil and gas sphere. Ferrous and nonferrous metallurgy produces the most important construction materials for other industries and at the same time keeps up the demand for highly-qualified workers with rather high level of wages. The goal of the research is to identify the contribution of large companies of non-ferrous metallurgy to revenues of the Russian Federation budget system. For this end the authors analyzed accounts of companies with budget system on profit tax, on value-added tax, tax on individuals and tax on company property. Information base of the research was formed by works of home and overseas authors that show the role of large corporations in social and economic development of regions and countries, Rosstat data, information of the Federal Taxation Service on the Irkutsk region and the Krasnoyarsk territory, official annul and finance accounting of the public company ‘OK RUSAL’ and the public company ‘Norilsk Nickel’.